Development of an Anisotropic Porous Model of a Single Cow for Numerical Barn Simulations—A Numerical Study - Julian Hartje (Fluids)
Computational fluid dynamics (CFD) can be used to analyze the airflow patterns within a naturally ventilated cattle barn in detail, taking into account the influence of the animals. Typically, animals are modelled either as solid obstacles or as a porous block representing the entire animal-occupied zone (AOZ). In the latter approach, extensive pre-simulations are required to determine the appropriate resistance parameters. This study developed a cow model that captures the general influence of the animals, is easy to implement without the need for extensive pre-simulations, and can be applied to various barn types and herd sizes. It is based on a porous block for a single animal. The anisotropic parameters for pressure drop and heat flux were derived from a simplified 3D cow model under different wind speeds, flow directions, cow positions, and ambient temperatures. These parameters were then incorporated into the newly developed porous cow model using regression curves. A comparison between the solid and porous modelling approaches in a randomly selected AOZ showed good agreement in terms of pressure drop and downstream temperature distribution.